Dynamic factor models with time-varying parameters: Measuring changes in international business cycles - Marco Del Negro; Christopher Otrok (Federal Reserve Bank of New York, 2008)
We develop a dynamic factor model with time-varying factor loadings and stochastic volatility in both the latent factors and idiosyncratic components. We employ this new measurement tool to study the evolution of international business cycles in the post-Bretton Woods period, using a panel of output growth rates for nineteen countries. We find 1) statistical evidence of a decline in volatility for most countries, with the timing, magnitude, and source (international or domestic) of the decline differing across countries; 2) some evidence of a decline in business cycle synchronization for Group of Seven (G-7) countries, but otherwise no evidence of changes in synchronization for the sample countries, including European and euro-area countries; and 3) convergence in the volatility of business cycles across countries.
Keywords: C11; C32; F02; 330; Bayesian factor models; time-varying parameters; Great Moderation; international business cycles